Clinical pharmacokinetics of oral azithromycin in epididymal tissue. Issue 10 (October 2019) - Sadahira, Takuya; Wada, Koichiro; Ikawa, Kazuro; Morikawa, Norifumi; Mitsui, Masao; Araki, Motoo; Fujiyoshi, Masachika; Ishii, Ayano; Watanabe, Masami; Watanabe, Toyohiko; Nasu, Yasutomo
Abstract: Objectives: Chlamydia trachomatis is one of the major pathogens causing acute epididymitis. Azithromycin (AZM) has a good efficacy against C. trachomatis ; however, the ability of AZM to penetrate into human epididymal tissue has not yet been fully elucidated. Here, we examined the appropriate dosage of oral AZM for human epididymal tissue by site-specific pharmacokinetic/pharmacodynamic (PK/PD) analysis. Methods: Patients with prostate cancer who underwent orchiectomy were included in this study. All patients received a 1-g dose of AZM before orchiectomy. Both epididymal tissue and blood samples were collected during surgery, and the drug concentrations were measured by high-performance liquid chromatography. All concentration-time data were analyzed with a three-compartment model with first-order absorption and elimination processes to simulate AZM concentrations in serum and epididymal tissue. Results: A total of 10 patients were enrolled in the current study. For the observed values, the ratio of the epididymal concentration to the serum concentration was 5.13 ± 3.71 (mean ± standard deviation). For the simulated values, the maximum concentrations were 0.64 μg/mL at 2.42 h in serum and 1.96 μg/g at 4.10 h in epididymal tissue. The 24-h concentrations were 0.239 μg/mL in serum and 0.795 μg/g in epididymal tissue. Conclusions: The penetration of oral AZM into human epididymal tissue was examined to assess the potential application of AZM for the treatment of acute epididymitis. Based on the previous reports mentioning drug-susceptibility of C. trachomatis, multiple doses of oral AZM 1 g would be recommended for epididymitis based on the site-specific PK/PD.